NILAI NILAI PENDIDIKAN AGAMA ISLAM DALAM BUKU QURANIC LAW OF ATTRACTION MERAIH ASA DENGAN ENERGI KALAM ILAHI KARYA RUSDIN S.RAUF - Kunti Anisatul Qulub; Rifqi Muntaqo; Ali Imron (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to examine three main aspects: the concept of Islamic Religious Education, the content of the book “Qur'anic Law of Attraction: Achieving Hope with Divine Energy” by Rusdin S. Rauf, and the values of Islamic Religious Education contained in the book. The approach used is qualitative literature-based research, with data collection techniques through analysis of relevant sources and data. The results of the study show that the concept of Islamic Education is a structured process to instill Islamic values comprehensively, covering social, moral, intellectual, and spiritual aspects based on the Qur'an and Sunnah of the Prophet Muhammad SAW. The book “Qur'anic Law of Attraction” discusses how humans can achieve a better life through the principles of the Qur'an, emphasizing the difference from the Western version which relies on the power of the mind and affirmations; the Quranic version emphasizes prayer, gratitude, and patience. The values of Islamic Religious Education in this book include worship through prayer as a means of drawing closer to Allah SWT, as well as morals that involve gratitude for His blessings and patience in obeying His commands and avoiding His prohibitions.